Challenges to religious liberty in the twenty-first century - Bradley, Gerard V., 1954- (Cambridge : Cambridge University Press, 2012)
'Almost everyone today affirms the importance and merit of religious liberty. But religious liberty is being challenged by new questions (for example, use of the niqab or church adoption services for same-sex couples) and new forces (such as globalization and Islamism). Combined, these make the meaning of religious liberty in the twenty-first century uncertain. This collection of essays by ten of the world's leading scholars on religious liberty takes aim at these issues. The book is arranged around five specific challenges to religious liberty today: the state's responsibility to prevent coercion and intimidation of believers by others within the same faith community; the U.S.'s basic moral responsibilities to promote religious liberty abroad; how to understand and apply the traditional right of conscientious objection in today's circumstances; the distinctive problems presented by globalization; and the viability today of an'originalist' interpretation of the First Amendment religion clauses'--
Includes bibliographical references and index.
Keywords: Freedom of religion